Pendekatan Komunikasi Antar Budaya pada Peran Public Relation SMP Bahagia Jakarta dalam Menciptakan Nama Baik Sekolah - Nuruzzamani, Lutfiah; Pambudi, Satria; Aliyyawaly, Rahmadaniyah (Jurnal Ilmu Komunikasi, 2024)
Communication is certainly an important factor that must be possessed by a Public Relations to carry out its role. Creating a good name for the agency is one of the tasks that must be carried out by Public Relations. The purpose of this study was to examine the role of public relations at SMP Bahagia in creating a good name for the school among the Kayu Jati community. This research is a qualitative research. The method used in this study is descriptive analysis, data collection was carried out by conducting direct interviews with informants and the results of the interviews were analyzed using an intercultural communication approach. The result of this study is that SMP Bahagia Public Relations is considered important in maintaining the good name of the institution. SMP Bahagia public relations always provides information and educates the public about the advantages of SMP Bahagia and its students. The intercultural communication approach used by SMP Bahagia Relations is good. SMP Bahagia public relations understands cultural diversity and accepts differences or opinions from parents, students and the surrounding community. This had a good impact on improving the image of SMP Bahagia in the community.